More than just a bag: Understanding the Personalities of Eco-Entrepreneurs Behind Sustainable Leather Goods - Pati, Crispianus Padi; Presetyo, Ridwan Hanif; Moningka, Wela; Andriyani, Andriyani (Master of Management Diponegoro University, 2024)
This article provides an understanding of the relationship between circular economy, personality traits, and big five personality traits within the framework of the Theory of Planned Behavior (TPB) to give birth to Eco Entrepreneurs. By utilizing qualitative methods, this research explores an in-depth view of how certain personality characteristics can influence a person's intentions. to start a business that focuses on environmental sustainability. Data collection was carried out through in-depth interviews with the owner of Rorokenes, a leather goods business. Bridged by a phenomenological approach, this research found that several personality characteristics, such as Proactiveness, Need for Achievement, Self-efficacy and several personality traits of the Big Five personality traits theory such as Conscientiousness, Openness to Experience and Agreeableness intersect with the Circular Economy concept to form an Eco Entrepreneur. The results of this research have important implications for policy development, management practices, and educational approaches in promoting green entrepreneurship. This research also provides a theoretical contribution to the literature on green entrepreneurship by incorporating an understanding of the aspects of individual behavior that drive individual intentions to entrepreneurship in the green domain.